An unexplained death after routine cardiac surgery: how long have we dealt with coronavirus disease 2019?. (1st November 2020) - Varela Barca, Laura; Torralba Cloquell, Isabel; Herrero Cereceda, Jaime; Sáez de Ibarra, Jose Ignacio
Abstract: We present a case report of fatal respiratory failure after cardiac surgery in the early stages of the coronavirus disease 2019 outbreak. Although not supported by epidemiological data nor clinical course, coronavirus disease 2019 infection was revealed post-mortem by immunohistochemical detection of the severe acute respiratory syndrome coronavirus 2 spike protein in lung tissue. Abstract : On 30 January 2020, a 76-year-old woman was presented to a secondary referring hospital with dyspnoea and ventricular tachycardia.